A randomized controlled trial of Theracal LC compared to MTA for pulpotomy in immature permanent teeth with complica-ted crown fracture - WU Cui, LI Changshun, ZHANG Xin (Kouqiang yixue)
Objective To explore the long-term clinical effect of Theracal LC on complicated crown fracture of immature permanent teeth. Methods A total of 33 teeth (13 males,15 teeth; 16 females, 18 teeth) from 29 adolescent patients with complicated crown fracture were collected. In this randomized clinical trial, all the samples were divided into two groups depending on the different pulp capping materials: the experimental group-Theracal LC(n=17) and the control group-MTA(n=16), with the same contralateral or adjacent teeth as blank control group. The treated teeth were evaluated clinically and radiographically at 3, 6, 12, 24, 36, 48 months. Results During the 4-year follow-up, clinical symptoms of all the treated teeth in both groups improved and disappeared. At 6 months, the clinical success rate of both groups was 100%. The clinical success rate was 93.7% at 12 months in the MTA group. The clinical success rates of Theracal LC group at 12 months and 24 months were 94.1% and 88.2%, respectively. There was no statistical difference between the groups in clinical efficacy(P>0.05). The samples of MTA group went black, while Theracal LC group had no discoloration. The formation rate of early-formed dentine bridge in Theracal LC group was relatively faster than that in MTA group. The dentine bridge could be seen in all samples of both groups in the long term. The dentine bridges in Theracal LC group had complex morphology, while the linear uniform was mostly seen in MTA group. Conclusion As a pulp capping agent, Theracal LC has good clinical efficacy and biosafety,and can be used as one of the substitutes for MTA.